Can Other Comprehensive Income Affect Dividend Payments in Indonesia? - Marhaendra Kusuma; Beby Hilda Agustin (Share: Jurnal Ekonomi dan Keuangan Islam, 2023)
The concept of Other Comprehensive Income (OCI) refers to the difference between the fair value and historical value of assets, resulting from applying fair value principles in financial statement preparation. Despite being unrealized income, it affects equity, and some of its items have a real potential to be realized in the coming period. Previous research has mainly studied the effect of realized income (net income) on dividends, while the impact of unrealized income on dividends, especially in Indonesia, has received limited attention. This study investigates the relationship between OCI and dividends for 682 companies listed on the Indonesia Stock Exchange using data from annual reports spanning from 2015 to 2021. This study employs descriptive statistics, correlation analysis, multiple linear regression analysis, and path analysis to examine the mediating role of profitability and operating cash flows in the relationship between OCI and dividends. The results reveal that OCI, as a whole, does not have a significant impact on dividends. However, when analyzing only the items within OCI that are "to be reclassified to net income", specifically gains (losses) on “available-for-sale financial assets”, the study identifies a significant and positive relationship between OCI and dividends. These findings suggest that incorporating OCI with net income in the income statement format can enhance the relevance of financial information for users, emphasizing the importance of considering the impact of unrealized income on dividends and the mediating role of profitability and operating cash flows.========================================================================================================ABSTRAK – Dapatkah Other Comprehensive Income Mempengaruhi Pembayaran Dividen di Indonesia? Konsep Other Comprehensive Income (OCI) merujuk pada perbedaan antara nilai wajar dan nilai historis aset, yang dihasilkan dari penerapan prinsip nilai wajar dalam penyusunan laporan keuangan. Meskipun merupakan penghasilan yang belum direalisasi namun mempengaruhi ekuitas dan beberapa item diantaranya ada potensi nyata terealisasi di periode yang akan datang. Kajian sebelumnya, terutama di Indonesia, umumnya hanya menguji pengaruh pendapatan yang terealisasi terhadap dividen, sedangkan pengaruh pendapatan belum terealisasi belum banyak dieksplorasi. Kajian ini bertujuan untuk meneliti hubungan antara OCI dan dividen pada 682 perusahaan yang terdaftar di Bursa Efek Indonesia menggunakan data dari laporan tahunan selama periode 2015- 2021. Analisis data dilakukan dengan statistik deskriptif, analisis korelasi, analisis regresi linear berganda, dan analisis jalur untuk mengeksplorasi peran mediasi variabel profitabilitas dan arus kas operasi dalam hubungan antara OCI dan dividen. Hasil kajian menunjukkan bahwa secara keseluruhan, OCI tidak memiliki dampak signifikan terhadap dividen. Namun, ketika analisis hanya dilakukan pada item-item OCI kelompok “yang akan direklasifikasi ke laba bersih”, khususnya pada item keuntungan (kerugian) aset keuangan tersedia untuk dijual, OCI berpengaruh positif signifikan terhadap dividen, dan profitabilitas serta arus kas operasi juga memediasi pengaruh OCI terhadap dividen. Temuan ini menunjukkan bahwa menggabungkan OCI dengan laba bersih dalam format laporan keuangan dapat meningkatkan relevansi informasi keuangan bagi pengguna, dengan menekankan pentingnya mempertimbangkan dampak penghasilan yang belum direalisasi pada dividen dan peran mediasi dari profitabilitas dan arus kas operasi.